Unified Programming Environment for Heterogeneous Distributed Parallel Systems - Hirasawa, Shoichi; Honda, Hiroki (2008 International Workshop on Innovative Architecture for Future Generation High-Performance Processors and Systems, 2008)
Parallel execution environment, such as the multi-core CPU, a cluster, and a grid, has spread increasingly. The change from a homogeneous core based CPU and a shared memory to the distributed memory and the heterogeneous core based CPU is making system architecture complicated. The programming interface and programming model which are different in each parallel execution environment are used. Since this serves as a burden for users, it has barred the spread of parallel execution environment. In this paper, the execution model which treats such system architecture systematically is explored. This performs the unified programming interface for heterogeneous distributed memory system architecture.